Gender Diversity in Leadership Positions and Organizational Success: The Mediating Role of Employee Engagement and Innovation (International Journal of Food and Nutritional Sciences, 2021)
Gender diversity in leadership has become a strategic priority for organizations seeking sustainable competitive advantage. Although previous studies have examined the association between female leadership representation and firm performance, findings remain inconsistent across industries and geographical contexts. This study investigates the influence of gender diversity in leadership positions on organizational success, with employee engagement and innovation capability acting as mediating variables. The research adopts a quantitative approach using survey responses collected from employees and managers across multiple industries. Structural Equation Modeling (SEM) is proposed to examine the relationships among leadership diversity, employee engagement, innovation, and organizational performance. The study contributes to diversity and leadership literature by providing an integrated framework explaining how gender-diverse leadership influences organizational outcomes. The findings are expected to offer practical implications for policymakers, human resource managers, and organizational leaders.